Microbiome analysis of bronchoalveolar lavage (BAL) specimens from immunocompromised patients with pneumonia compared to those from healthy volunteers - Zareen Fatima; Matthew D. Surette; Sarah Marttala; Daniela Leto; Padman Jayaratne; Fiona Smaill; Marek Smieja; Mohammad Rubayet Hasan (PLoS ONE, 2026)
Background Metagenomic sequencing of bronchoalveolar lavage (BAL) specimens is increasingly being applied for the diagnosis of lower respiratory tract infections, offering agnostic pathogen detection and a faster turnaround time. While metagenomic sequencing of BAL specimens can reveal a wide range of organisms, their clinical relevance is often unclear because of the challenge of distinguishing true pathogens from background taxa. This study compared the BAL microbiomes of immunocompromised patients with pneumonia to those of healthy volunteers, with the aim of assisting clinical interpretation of metagenomics-based approaches for diagnosing pneumonia in this patient population. Methods BAL specimens from healthy control volunteers (n = 20) were collected during a COVID-19 vaccine trial, while residual BAL specimens from immunocompromised patients (n = 52) were obtained from the Hamilton Regional Laboratory Medicine Program (HRLMP) after standard culture and PCR testing. 16S rRNA gene amplicon sequencing was performed using Nanopore technology. Reads were classified using Minimap2 in EPI2ME, and microbiome analyses were conducted using the vegan and MaAsLin2 packages in RStudio (v2026.1.1.403). Results Immunocompromised patients showed significantly lower bacterial read counts and reduced alpha diversity (p < 0.0001; Wilcoxon Rank-Sum test), along with higher inter-sample heterogeneity. In contrast, BAL samples from healthy controls exhibited a more homogeneous microbial profile dominated by anaerobic Gram-negative genera, including Prevotella, Veillonella, Selenomonas , and Fusobacterium . Beta diversity analyses using Bray–Curtis and Jaccard distance metrics demonstrated significant compositional separation between cohorts (PERMANOVA p = 0.001), with tight clustering of healthy controls and marked dispersion among immunocompromised samples. Differential abundance analysis identified 96 significantly altered species (q < 0.05), with immunocompromised patients showing depletion of anaerobic commensals and enrichment of clinically relevant pathogens, including Stenotrophomonas maltophilia , Enterococcus spp., Mycoplasma spp., and Nocardia spp. Conclusion Immunocompromised patients demonstrated a markedly disrupted and heterogeneous BAL microbiome, characterized by a loss of anaerobic commensals and an enrichment of potentially pathogenic taxa. This study provides a characterization of the dysbiotic state in immunocompromised pneumonia, offering a baseline reference for future longitudinal studies and clinical trials aimed at improving the interpretation of metagenomic findings in this patient population.